Multi-frequency, multi-epoch VLBI observations of the M87 jet. Issue Volume 9:Issue S304(2013) (25th July 2014) - Hada, Kazuhiro; Giroletti, Marcello; Giovannini, Gabriele; Doi, Akihiro; Kino, Motoki; Nagai, Hiroshi; Honma, Mareki; Kawaguchi, Noriyuki
Abstract: We present some of preliminary results obtained by our dense monitoring project of the M87 jet with VERA 22 and 43 GHz starting from October 2010. The aims of this monitor are to clarify the detailed physical properties of the M87 jet base near the black hole, including the connection to γ-ray productions, jet kinematics and nuclear opacity. We detected a remarkable increase of the radio flux from the jet base of M87 during an elevated very-high-energy γ-ray activity occurred in the early 2012, suggesting that the γ-ray is produced in the immediate vicinity of the central black hole.